Analysis of the performance of operators who do not work according to the Standard Operating Procedure which causes Not Good products to be delivered to customers using the 5W + 1H method - Hikam, Amar Syaifullah; Ramadhani, Muhammad Naufal; Azis, Abdul; Nst, Mhd Fachrur Rozi; Kurniawan, Varas Pratama Putra; Prastyo, Yudi (Lentera Ilmu Nusantara, 2024)
PT QWERTY always strives to maintain production quality and quantity by paying attention to the performance of all employees, especially production operators. However, during the production process, NG / Abnormal is still often found, production targets are not achieved, and NG products are sent to customers (Customer Claims). This happens because human error such as employee performance that does not comply with SOPs, working in a hurry, and even in some cases, employees are sleepy, especially when working the night shift, are also the cause. This study aims to analyze the performance of operators who do not work in accordance with the Standard Operating Procedure (SOP) in the production process. This study uses the 5W + 1H method. The 5W+1H method is an information gathering and analysis technique that includes six basic questions, namely What, Who, When, Where, Why, and How. The results of the analysis show that violations of SOPs by operators can trigger errors in the production process, leading to NG products being delivered to customers. The main factors that trigger non-compliance with SOPs include lack of training, high workload, and lack of regular monitoring and evaluation of performance.